Phenotype-Guided Management of Atrial Fibrillation in Heart Failure: From Rate Control to Catheter Ablation - Ebru Şahin; İsa Ardahanlı; Onur Akhan; Ramazan Aslan; Mustafa Kaplangöray (Journal of Clinical Medicine, 2026)
Atrial fibrillation (AF) and heart failure (HF) frequently coexist, but the clinical relevance of AF may differ according to whether it appears to be a potentially reversible contributor, an aggravating factor in established HF, or a marker of advanced substrate. The driver–modifier–marker lens used in this review is a provisional, nonvalidated aid to clinical reasoning and should not be interpreted as a treatment score. This narrative review was informed by dated searches of PubMed/MEDLINE, the Cochrane Library, and OpenAlex through 29 July 2026, followed by a targeted update on 30 July 2026. It considers HF with reduced, mildly reduced, and preserved ejection fraction together with AF timing, burden, ventricular-rate exposure, myocardial substrate, and reversibility. Early rhythm control may be particularly relevant when AF is recent or temporally associated with ventricular dysfunction, symptoms, decompensation, or inadequate cardiac resynchronization therapy delivery. Evidence supporting catheter ablation is most direct in suspected AF-mediated cardiomyopathy and selected HFrEF populations, whereas evidence in HFpEF more consistently supports symptom relief, improved exercise hemodynamics, and AF-burden reduction than mortality reduction. Pulmonary vein isolation remains the procedural foundation. Radiofrequency, cryoballoon, and pulsed-field ablation are effective in broad AF populations, but HF phenotype-specific prognostic superiority has not been established for any energy source. Clinical decisions should reflect the design and directness of the evidence together with expected benefit, rhythm durability, procedural risk, patient-reported outcomes, stroke prevention, guideline-directed HF therapy, risk-factor management, and patient preference.